Isolation and in vitro assessment of chicken gut microbes for probiotic potential - Shahbaz, Fatima; Muccee, Fatima; Shahab, Aansa; Safi, Sher Zaman; Alomar, Suliman Yousef; Qadeer, Abdul (Frontiers in Microbiology, 2024)
Poultry production occupies an important place in the economy of any country. High broiler production in recent years has badly affected its profitability due to bad feed quality, excessive use of chemotherapeutic agents, emergence of diverse pathogens and the deficiencies in management practices during rearing cycle. Microbiological improvement of the meat quality using potential probiotics can prove beneficial for broilers farming. Present study was initiated to isolate chicken GIT bacteria with probiotic potential. To isolate probiotics from chicken gut, alimentary canal of chickens of known sizes and ages was suspended in Ringers soln. under shaking conditions for overnight followed by serial dilutions of ringers soln. Bacteria were analyzed via growth curve analysis, biochemical tests, molecular characterization, antimicrobial activity assay, antibiotic sensitivity assay, GIT adherence assay, bile salt and gastric acid resistant assay and cholesterol assimilation assay. Four bacteria isolated in present study were identified as Limosilactobacillus antri strain PUPro1, Lactobacillus delbrueckii strain PUPro2, Lacticaseibacillus casei strain PUPro3, and Ligilactobacillus salivarius strain PUPro4. L. delbrueckii strain PUPro2 grew extremely fast. All isolates exhibited exceptional resistance to increasing concentrations of NaCl and bile salts with p-value > 0.5. L. delbrueckii strain PUPro2 adhered to chicken ileum epithelial cells and demonstrated the highest viable counts of 320 CFUs.Antagonistic action was found in all isolates against P. aeruginosa, B. subtilis, B. proteus, and S. aureus, with p-value > 0.5. Antibiotic susceptibility testing showed sensitivity to all the antibiotics used. Cholesterol assimilation was detected in all bacteria, with values ranging from 216.12 to 192.2 mg/dl. All isolates exhibited γ-hemolysis. In future, these bacteria might be tested for their impact on broilers meat quality and growth and can be recommended for their use as supplements for broilers diet with positive impact on poultry production.